2011
DOI: 10.1161/circulationaha.111.031229
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role for Stromal Interaction Molecule 1 in Cardiac Hypertrophy

Abstract: Background Cardiomyocytes (CM) utilize Ca2+ not only in excitation-contraction coupling (ECC), but also as a signaling molecule promoting for example cardiac hypertrophy. It is largely unclear how Ca2+ triggers signaling in CM in the presence of the rapid and large Ca2+ fluctuations that occur during ECC. A potential route is store-operated Ca2+ entry (SOCE), a drug-inducible mechanism for Ca2+ signaling that requires stromal interaction molecule 1 (STIM1). SOCE can also be induced in cardiomyocytes, which pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
196
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(229 citation statements)
references
References 52 publications
14
196
2
1
Order By: Relevance
“…The existence of SOCE and expression of both STIM1 and Orai1 have also recently been shown to occur in HL-1 cardiomyocytes, an immortalized mouse atrial cell line (120). We and others have shown that in neonatal cardiomyocytes Ca 2ϩ store depletion induced STIM1 puncta formation, consistent with that seen in nonexcitable cells (37,153). We also demonstrated that in neonatal cardiomyocytes SOCE was highly selective for Ca 2ϩ , confirming that SOCE was primarily mediated by STIM1-Orai1 coupling rather than STIM1-TRPC1 (153).…”
Section: Orai1/trpcsupporting
confidence: 87%
See 2 more Smart Citations
“…The existence of SOCE and expression of both STIM1 and Orai1 have also recently been shown to occur in HL-1 cardiomyocytes, an immortalized mouse atrial cell line (120). We and others have shown that in neonatal cardiomyocytes Ca 2ϩ store depletion induced STIM1 puncta formation, consistent with that seen in nonexcitable cells (37,153). We also demonstrated that in neonatal cardiomyocytes SOCE was highly selective for Ca 2ϩ , confirming that SOCE was primarily mediated by STIM1-Orai1 coupling rather than STIM1-TRPC1 (153).…”
Section: Orai1/trpcsupporting
confidence: 87%
“…The putative physiological and pathophysiological roles of SOCE and STIM1 that have been identified to date are summarized in Table 1. A number of studies have recently reported the presence of STIM1 in adult cardiomyocytes (37,59,153), and consistent with earlier evidence supporting a role for SOCE in regulating cardiac hypertrophy (38), STIM1 levels were shown to be increased in response to cardiac hypertrophy (37, 59). Nevertheless, despite evidence that SOCE exists in cardiomyocytes, its wider acceptance as a contributor to cardiomyocyte Ca 2ϩ homeostasis remains limited.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Previously, research in rodent models has demonstrated that SOCE, STIM1, and Orai1 play crucial roles in the development of cardiomyocyte hypertrophy [8][9][10], whereas NO, cGMP, and PKG exert antihypertrophic effect [6,11,34]. However, one of the challenges in exploring mechanistic insight of Orai1 and/or NO-cGMP-PKG effect is lack of human cardiomyocytes for research.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease of Ca 21 in sarco/endoplasmic reticulum causes STIM1 oligomerization and relocalization to the regions immediately underneath the plasma membrane, where it interacts with Orai1 to induce Ca 21 entry [8]. Interestingly, both STIM1 and Orai1 are reported to play essential roles in promoting cardiomyocyte hypertrophy [9,10].…”
Section: Introductionmentioning
confidence: 99%